Studies on Formation and Thermal Decomposition of Lead Hydride, PbH4 - Narsito Narsito (Indonesian Journal of Chemistry, 2001)
In the present work, some fundamental aspects of the formation of gaseous lead hydride from aqueous solutions containing divalent lead ions (Pb2+) and its application in the atomic absorption spectrometric analysis lead has been investigated. By utilizing a peristaltic pump, an acidic solution of Pb2+ was first oxidized with ammonium peroxodisulphate, NH4S2O8, and followed by reduction with sodium tetrahydroborate, NaBH4. After a gas-liquid separation, the gaseous lead hydride produced was directly swept into an electrically heated open ended quartz tube, located at the light path of an atomic absorption spectrometer in order to have possibilities for specific atomic absorption spectroscopic measurements. The absorbance signals caused by lead atomic absorption could be used proportionally to estimate the density of atomic lead vapor produced in the thermal decomposition under investigation. Results showed that on-line pre-oxidation of the analyte is very important and crucial step in the gaseous hydride generation of lead, and no lead hydride was produced without the involvement of this step. Moreover, it was observed that the use of low major gas flows cannot be applied in quantitative atomic absorption spectrometric determination of lead by this technique. This condition may result in possible losses of the analyte atomic vapor due to metallic condensation.